The relationship between corporeality and digital technologies in immersive exhibitions: giving new meaning to art and its narratives of communication, language and spectacle - Bastos, Sandra Regina (Revista do Colóquio, 2024)
The theme of corporeality is inserted in the context of immersive exhibitions, as it considers the body in movement that establishes an inseparable relationship between the physiological and psychological effects and the scenarios presented. This article intends to analyze and specifically address the scenography of immersive spaces that indicates different concepts, meanings and experiments that allow the public to interact and dialogue with the images. To this end, we use the methodology of historical research supported by various visits to immersive exhibitions where we experience the viewer’s interaction with the works, the artist and the space. It is concluded that technologies are fundamental and constitute determining agents of this immersive experience, giving new meaning to contemporary art and its narratives. Keywords: Corporeality, Exhibitions, Immersive, Art, Education.